Faktor Pencetus Kejadian Alergi Pernapasan Pada Pasien Dewasa Di RSUPN Dr. Cipto Mangunkusumo: The Triggering Factors of Respiratory Allergiesin Adult Patients at the RSUPN Dr. Cipto Mangunkusumo - Fithriyah Nur Kurnia; Alex Hartana; Iris Rengganis (Departemen Biologi, Institut Pertanian Bogor, 2019)
Allergy is a hypersensitive reaction in human due to human body produced IgE antibody more than regullary do as a response to the presence of allergens. Asthma and rhinitis are respiratory allergies, could be caused by genetics and environmental factors. The objectives of this study was to analyze the trigger factors of asthma and rhinitis patients at the Allergy-Immunology Polyclinic, Internal Medicine Department, Faculty of Medicine, University of Indonesia, Dr. Cipto Mangunkusumo National Center General Hospital, Jakarta. The skin test using grass mix pollen, cat, dog, cockroach, and dust mites allergens were done to 90 respiratory allergy patients. History of respiratory allergy from their parents, and environmental factors such as pets, cigarette smoke, and emotional state were asked and recorded. The patients mostly women, and most respiratory allergy patients could be detected by skin test using dust mites allergens, however, their reaction did not the same for other allergens. More than 50% patients of respiratory allergy have atopy from their parents, for most of patients, their emotional state and cigarette smoke in house could trigger the symptom of respiratory allergy.